2016
DOI: 10.1074/jbc.c116.726091
|View full text |Cite
|
Sign up to set email alerts
|

Helicase Activity Plays a Crucial Role for RNase R Function in Vivo and for RNA Metabolism

Abstract: RNase R is a 3 to 5 hydrolytic exoribonuclease that has the unusual ability to digest highly structured RNA. The enzyme possesses an intrinsic, ATP-dependent RNA helicase activity that is essential in vitro for efficient nuclease activity against double-stranded RNA substrates, particularly at lower temperatures, with more stable RNA duplexes, and for duplexes with short 3 overhangs. Here, we inquired whether the helicase activity was also important for RNase R function in vivo and for RNA metabolism. We find … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The helicase activity utilizes the same catalytic channel as the nuclease activity, and is an intrinsic component of the enzyme’s ability to digest structured RNAs since mutations that interfere with ATP binding prevent digestion of structured RNA, but have no effect on the digestion of single-stranded RNA molecules (Hossain et al 2016). Escherichia coli strains in which the helicase activity of RNase R has been eliminated by mutation of the Walker motifs exhibit growth defects at low temperatures (Hossain and Deutscher 2016). Moreover, cells also lacking PNPase and dependent on RNase R for growth, do not grow at 31 °C, and grow extremely poorly at 34, 37, and 42 °C.…”
Section: Escherichia Coli Exoribonucleasesmentioning
confidence: 99%
See 2 more Smart Citations
“…The helicase activity utilizes the same catalytic channel as the nuclease activity, and is an intrinsic component of the enzyme’s ability to digest structured RNAs since mutations that interfere with ATP binding prevent digestion of structured RNA, but have no effect on the digestion of single-stranded RNA molecules (Hossain et al 2016). Escherichia coli strains in which the helicase activity of RNase R has been eliminated by mutation of the Walker motifs exhibit growth defects at low temperatures (Hossain and Deutscher 2016). Moreover, cells also lacking PNPase and dependent on RNase R for growth, do not grow at 31 °C, and grow extremely poorly at 34, 37, and 42 °C.…”
Section: Escherichia Coli Exoribonucleasesmentioning
confidence: 99%
“…Although very little work has been carried out on expression of the rnr gene (Cairrao et al 2003; Cairrao and Arraiano 2006), it appears to be part of an operon that contains the nsrR gene (coding for a NO-dependent transcriptional repressor) upstream, and rlmB (encoding a 23S rRNA methyltransferase) and yjfI downstream. Mutant strains lacking RNase R grow essentially normally at temperatures between 31 and 42 °C, but display slowed growth at temperatures of 25 °C and below (Cairrao et al 2003; Hossain and Deutscher 2016). In contrast, a mutant strain lacking both RNase R and PNPase does not grow (Cheng and Deutscher 2003), suggesting overlap in an essential cellular function.…”
Section: Escherichia Coli Exoribonucleasesmentioning
confidence: 99%
See 1 more Smart Citation
“…High levels of rRNA degradation fragments have been observed before in pnp ts Δ rnr strains ( 24 ), but those studies left open the possibility that they could have arisen due to the treatment applied to inactivate PNPase, a condition that leads to growth cessation. Similarly, rRNA fragment accumulation has also been observed in strains that lack PNPase and contain mutations in RNase R that inactivate its helicase activity, but these strains exhibit a four-fold increase in cell doubling time ( 38 ). In contrast, another study found undetectable levels of rRNA degradation over several hours of cell growth ( 31 ).…”
Section: Discussionmentioning
confidence: 98%
“…The helicase activity does not require the hydrolytic exoribonuclease activity; however, the nuclease activity on double-stranded RNA requires the helicase activity [ 43 ]. Importantly, the helicase activity is required in vivo especially at low temperature [ 44 ].…”
Section: All In One: Rnase Rmentioning
confidence: 99%